Preemptive Scheduling Policy for Multiple Loan Repayment - Ng, C. T. (Institutional Knowledge at Singapore Management University, 2012)
We study the multi-loan-repayment problem by formulating it as a single-machine scheduling problem with preemptive and time-dependent processing times to minimize the makespan. We transform the scheduling problem into a continuous non-linear optimization problem and obtain an approximate solution by solving a series of the corresponding linear programming problems. We also identify agreeable conditions for the problem and discuss the computational complexity of the problem.